The Fatality Index of Public Transport (Express Bus) in Malaysia - Ahmad Termida, Nursitihazlin (2006)
Until now, there is no research or study being conducted to establish the fatality index of public transport in Malaysia especially for express buses, For now, we only know the total accidents in our data storage involving public transport in Malaysia. Hence, this study has Been conducted to develop the safety index of public transport (express bus) in Malaysia. It is important to know the sakty index of public transport (express bus) in this country as compared to other developed countries since express bus is one of the main modes for long distance transportation in Malaysia. Besides, when the fataiity index is obtained in ths study, it could be used as a gu~delineo r reference to improve the safety level of public transport (express bus) in Malaysia, The data analysis in this study is done using Mileage Deaths Rate Method (MDR) and the measurement unit is in passenger kilometres travelled (PKT). Thus, the fatality index is stated as per billion PKT which has been used by Department for Transport of United Kingdom. In this study, the fatality index of public transport (express buses) in Malaysia is 0.000009 per billion PKT as compared to the fatality index in the Unitad Kingdom which is 0.4 per billion PKT for the year 2005. It shows that the use of express buses in Malaysia is much safer than the United Kingdom.